Evaluación funcional y efectos de un entrenamiento aeróbico en pacientes hemodializados con insuficiencia renal crónica - Novo, André (2010)
Chronic renal insufficiency is described by the loss of the kidney’s capacity of eliminating toxic substances, concentrating urine and preserving the electrolytes. It also occurs a change in tire remaining renal functions. This disease may vary from a light malfunction to a severe renal insufficiency and it may also lead to renal terminal insufficiency. Its evolution varies and it may take many years to achieve the kidney’s internal structures impairment or it can develop rapidly (Basile, 2008). In the early stages the disease can be asymptomatic In fact, progression can be so slow that tire symptoms only occur when the kidney looses 9O% of its function (Levin et al., 2008). By presenting a progressive condition, morbidity and mortality are significant (Snively and Gutiérrez, 2004).